Achilles tendon Z-plasty with rollover tensor fascia lata graft for correction of equinus foot deformity - Gupta, Madhusoodan; Goel, Ankur; Varshney, Deepti; Biswkarma, Vishal K. (International Surgery Journal, 2021)
Equinus deformity is a condition in which dorsiflexion movement of the ankle joint is limited or decreased. Equinus deformity arises due to contracture/shortening/tightening in achilles tendon or soleus muscles or gastrocnemius muscle. The lengthening procedure of the achilles tendon can be done by various techniques such as the open or percutaneous method and Z-plasty versus sliding technique. Here we reported a case of post-traumatic equinus deformity of the right foot. The patient’s dorsiflexion movement was restricted. In this case, the patient was operated for open Z-plasty of the achilles tendon with rollover tensor fascia lata graft for lengthening of the contracted achilles tendon. The patient was discharged on the third postoperative day uneventfully. After 7 months of follow-up, the patient was walking normally without limping with the full range of motion at the right ankle joint as similar to his left ankle joint.